PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KAHOOT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SEKOLAH DASAR - fatmawati, Nadhia; Muhamad Sudarshono; Aliya Rahmawati; Farahdila; Sri Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the impact of using the Kahoot learning media on the motivation of elementary school students. In today's digital era, educational technology is increasingly developing, and Kahoot has become one of the platforms widely used in the learning process. The method employed in this research is qualitative literature review, collecting and analyzing various sources, including articles, journals, and relevant books regarding Kahoot and learning motivation. The results indicate that the use of Kahoot can enhance students' learning motivation through the interactive elements and challenges it provides. Students feel more engaged and motivated to learn when using Kahoot, which positively affects their learning outcomes. This study concludes that the integration of Kahoot in learning can be an effective strategy to improve the motivation of elementary school students. Recommendations are provided for teachers to consider using Kahoot as an innovative and engaging learning media.